(untitled) (Global Journal of Management and Business Research, 2017)
This article investigates the influence of community banks’ micro credit on consumption of the beneficiaries. A survey is conducted in tracing the loan beneficiaries and estimating the pattern of change in their consumption in Bauchi State. Various items for consumption of the poor were identified and logged side by side with the OLS equation with a view to see the credit influence over a period of time. The result shows that micro credit and consumption of the poor are positively related. However, the outcome defends on many socio-economic characteristics of the borrowers.